Overcoming resistance against managed care: Insights from a bargaining model - Andree Ehlert; Thomas Wein; Peter Zweifel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
Recent healthcare reforms have sought to increase efficiency by introducing managed care (MC) as an alternative to conventional care. This article proposes an institutional change designed to let German consumers choose between the two settings through directing payments from the Federal Health Fund to social health insurers (SHIs) or to specialized MC organizations (MCOs). A game involving a SHI, a MCO, and a representative insured (RI) is analyzed. In a 'threeplayer/three-cake' game the coalitions SHI, MCO, MCO, RI, and SHI, RI can form. Players' possibility to switch between coalitions creates new outside options, causing the bilateral Nash bargaining solution to be replaced by the so-called von Neumann-Morgenstern triple.
Keywords: I13; I11; D02; C72; 330; Gesundheitsreform; Integrierte Versorgung; Nash-Gleichgewicht; Deutschland